3D culture models for studying branching morphogenesis in the mammary gland and mammalian lung. (April 2019) - Nerger, Bryan A.; Nelson, Celeste M.
Abstract: The intricate architecture of branched tissues and organs has fascinated scientists and engineers for centuries. Yet―despite their ubiquity―the biophysical and biochemical mechanisms by which tissues and organs undergo branching morphogenesis remain unclear. With the advent of three-dimensional (3D) culture models, an increasingly powerful and diverse set of tools are available for investigating the development and remodeling of branched tissues and organs. In this review, we discuss the application of 3D culture models for studying branching morphogenesis of the mammary gland and the mammalian lung in the context of normal development and disease. While current 3D culture models lack the cellular and molecular complexity observed in vivo, we emphasize how these models can be used to answer targeted questions about branching morphogenesis. We highlight the specific advantages and limitations of using 3D culture models to study the dynamics and mechanisms of branching in the mammary gland and mammalian lung. Finally, we discuss potential directions for future research and propose strategies for engineering the next generation of 3D culture models for studying tissue morphogenesis.